Manajemen Logistik dan Persepsi Konsumen Lembaga terhadap Pemasaran Asparagus oleh Koperasi Tani Mertanadi di Desa Plaga Kecamatan Petang Kabupaten Badung - NI MADE INDRI DIANI; I GUSTI AGUNG AYU AMBARAWATI; I NYOMAN GEDE USTRIYANA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Logistic Management and Organizational Consumer’s Perception on Asparagus Marketing by Farmer CooperativeAsparagus is a commodity that is commonly sold for modern markets. Mertanadi farmer cooperative is the only cooperative in Bali that supply asparagus to many destinations including supermarkets, hotels, restaurants and other suppliers. The commodity is supplied by the cooperative members at Plaga Village, Petang district, Badung regency. The aims of this study are to find out logistic management of asparagus by Mertanadi farmer cooperative to the organizational consumers. This research was carried out to 17 organizational consumers of Mertanadi cooperative located in Denpasar city, Badung regency and Gianyar regency. Logistic management by the cooperative was analyzed using descriptive qualitative method, while the perceptions of the consumers to the commodity were analyzed using Likert scale. Result of the study shows that the Mertanadi farmer coopertaive has implemented the seven basic concepts of logistic management including planning, budgeting, procurement, warehousing and distribution, maintenance and deletion as well as controlling. Perceptions of the organizational consumers seen from product availability, product quality and price are categorized good. However there is one weakness, according to the consumers, that is the cooperative is not able to fulfil the entire demand. It is expected that the cooperative needs to manage to fulfil the whole consumer’s demand.